Using the systemological basis and information entropy function in the study at uncertainty conditions of system-structured objects - Kozulia, T.V.; Kozulia, M.M. (Вопросы атомной науки и техники, 2022)
In the article substantiated the expediency of introducing the basics of systemological analysis in modeling and structuring of studies of complex objects, which allows to establish conditions for the implementation of a certain target function, which is responsible for the state and functionality of the investigated object in certain conditions of the environment, taking into account the macrostate of the complex system, through experiments of microstates, and its changes in the system “object – the environment” regarding the state of external systems using an entropy func-tion according to a consistent analysis of uncertainties and their solution to establish conditions for the stabilization of the object or achieve the goal of regulation situations based on information synergetics. It was concluded that, proposed comprehensive entropy-synergy analysis of the determination of the state “the investigated system – the environment” and changes in the consequence of process transformations in systemic objects in conditions of certain uncertainty does not require additional research, characteristic of known estimates for the criteria in widespread mathematical means decision-making. Розглянуто доцільність впровадження основ системного аналізу в моделюванні та структуруванні досліджень складних об’єктів, що дозволяє встановлювати умови для здійснення певної цільової функції, яка відповідає за стан та функціональність досліджуваного об’єкта в певних умовах навколишнього середовища, з урахуванням макростану складної системи, через експерименти мікростанів, та його зміни в системі «об’єкт - навколишнє середовище» щодо стану зовнішніх систем за допомогою функції ентропії відповідно до послідовного аналізу невизначеності і їх вирішення встановленням умов для стабілізації об’єкта або досягнення мети ситуацій регулювання на основі інформаційної синергетики. Було зроблено висновок, що запропонований комплексний аналіз ентропійно-синергетиного визначення стану «досліджувана системи - навколишнє середовище» та зміни внаслідок процесів трансформацій у системних об’єктах в умовах певної невизначеності не вимагає додаткових досліджень, характеристик для відомих oцінок для критеріїв у поширених математичних засобах прийняття рішень. Рассмотрена целесообразность внедрения основ системного анализа в моделировании и структурировании исследований сложных объектов, что позволяет устанавливать условия для осуществления определенной целевой функции, которая отвечает за состояние и функциональность исследуемого объекта в определенных условиях окружающей среды, с учетом макросостояния сложной системы, через эксперименты микросостояний, и его изменения в системе «объект - окружающая середа» по состоянию внешних систем с помощью функции энтропии в соответствии с последовательным анализом неопределенности и их решения определения условий для стабилизации объекта или достижения цели ситуаций регулирования на основе информационной синергетики. Был сделан вывод, что предложенный комплексный анализ энтропийно-синергетического определения состояния «исследуемая система - окружающая среда» и изменения вследствии процессов трансформаций в системных объектах в условиях некоторой неопределенности не требует дополнительных исследований, характерных для известной oценки критериев в распространенных математических методов принятия решений.